Bias-Free Solar-To-Hydrogen Peroxide Production Using Nanoporous BiVO4-Based Photoanode With Atomic Layer Deposited SnO2 - Wang, Jinghan; Kim, Jaehyun; Yang, Jin Wook; Park, So Jeong; Kim, Taeseok; Lee, Jiwoo; Cheon, Woo Seok; Kwon, Hee Ryeong; Jun, Sang Eon; Peng, Jiayue; Zou, Yu Lin; Shokouhimehr, Mohammadreza; et al. (Wiley-VCH Verlag, 2026)
Hydrogen peroxide (H2O2) is a green oxidant with an energy density comparable to that of compressed hydrogen, making it a promising candidate for chemical energy storage. Converting renewable energy into H2O2 via the photoelectrochemical water oxidation reaction offers a sustainable pathway, yet the competing oxygen evolution reaction limits the solar-to-chemical conversion (SCC) efficiency. Here, we develop a BiVO4 based photoanode combined with a conformal SnO2 passivation layer. A built-in electric field is established at the SnO2/BiVO4 heterojunction, which facilitates charge separation and promoting hole transport toward the SnO2 surface. The valence band edge of SnO2 is also thermodynamically favorable for H2O2 production. To further improve H2O2 production, a CaSnO3 cocatalyst is integrated on the photoanode, enabling enhanced reaction kinetics and selectivity toward 2e− water oxidation pathway. The resulting CaSnO3/SnO2/BiVO4 photoanode achieves an average Faradaic efficiency of 90% over wide potential range of 0.6–2.1 VRHE, with a H2O2 generation rate of 0.838 µmol cm−2 min−1 and a photocurrent density of 5.44 mA·cm−2 at 1.23 VRHE. Photoelectrochemical device composed of CaSnO3/SnO2/BiVO4 photoanode and perovskite/Si photovoltaic simultaneously produce H2O2 and H2 without applied bias, which achieving SCC efficiency of 1.12%, the highest record to date for bias-free H2O2 production at a single photoanode.